Model Perlindungan Hukum Konsumen Terhadap Periklanan Menyesatkan Di Surat Kabar (Studi Kasus Surat Kabar Solo Pos Di Surakarta) - Khoiruman, Muhammad, Prof. Dr. Harun Joko Prayitno, M.Hum, Kelik Wardiono, S.H., M.H (2015)
This study aims to describe and explanaing consumer protection against misleading advertisements in newspapers, and explaning describe how much advertising in newspapers in accordance with the legislation in providing legal protection for consumers. and explore models of newspaper advertising in the consumer protection perspective. This research is a normative-empirical, ie research by reviewing legislation, regulations discusses advertising and consumer protection as well as empirically explore the information in the field of ad impressions in the newspaper that is considered misleading, and make observations by distributing questionnaires and interview to the competent authorities to the problems of the study The results of this study signify that the protection of consumers against advertising in newspapers has been accommodated in the Undang-undang No. 8/1999 about consumer protection, the Undang-undang No. 40/1999 about PERS, Undang-undang No: 7 th 1196 About Food, and Regulation 69 of the Food Label and Advertisement. In this study proved that a lot of ads that aired in the newspapers, notwithstanding the prevailing Model of legal protection for consumers against misleading advertising in newspapers in this study are : Formation of advertising legislation , the establishment censors print media advertising , announce misleading advertising to the general public , the determination of the standardization of formats of advertisements in newspapers and increasing the role of non-governmental consumer protection agencies .